Draft Annual Plan 1976-77 Volume IV Industry and Mining Government of Jammu and Kashmir - Planning Commission (Planning Commission, 1976)
The detailed project reports have been got prepared and also broad agreement have been reached with the Forest Department for supplying 70,000 metric tonnes annually of soft wood for the project. The Industrial license for the project has been received from the Government of India and the work relating to updating of the Project report is being entrusted to a reputable firm of consultants and the updated reports are expected to be in the hands of the Corporation by the Middle of January, 1976.
Government of Jammu and Kashmir